1987
DOI: 10.1111/j.1365-2133.1987.tb04931.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticulate hyperpigmentation distributed in a zosteriform fashion: a new clinical type of hyperpigmentation

Abstract: We have recently seen two cases of hyperpigmentation in children, which was reticulate and distributed in a zosteriform fashion. As another two cases of hyperpigmentation of this kind in children have been reported previously, described as reticulate hyperpigmentation distributed in a zosteriform fashion, this gives a total of four cases of hyperpigmentation of this kind reported recently from Japan. These four cases differed from progressive cribriform and zosteriform hyperpigmentation, the condition which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…Since its first description, only a few cases of LWNH have been reported 3,7–11 . From a review of the literature, however, several reported cases with similar findings, but described under different names, have been found; these include reticulate hyperpigmentation distributed in a zosteriform fashion, 12 reticulate hyperpigmentation of Iijima, Naito and Uyeno, 13 zosteriform lentiginous nevus, 14 and zebra‐like hyperpigmentation 15 …”
Section: Discussionmentioning
confidence: 99%
“…Since its first description, only a few cases of LWNH have been reported 3,7–11 . From a review of the literature, however, several reported cases with similar findings, but described under different names, have been found; these include reticulate hyperpigmentation distributed in a zosteriform fashion, 12 reticulate hyperpigmentation of Iijima, Naito and Uyeno, 13 zosteriform lentiginous nevus, 14 and zebra‐like hyperpigmentation 15 …”
Section: Discussionmentioning
confidence: 99%
“…350 Another study in which pigmentary anomalies along the lines of Blaschko were associated with abnormalities of the central nervous system included a few patients with incontinentia pigmenti and hypomelanosis of Ito; most cases could not be categorized further. 470 Included in the patterned hypermelanoses are cases reported as 'linear and whorled nevoid hypermelanosis', 463,465,[471][472][473][474][475][476][477][478][479] 'reticulate hyperpigmentation distributed in a zosteriform fashion', 480 'progressive cribriform and zosteriform hyperpigmentation', 481,482 'congenital curvilinear palpable hyperpigmentation', 483 'zebra-like hyperpigmentation', 484 'progressive zosteriform macular pigmented lesions', 485 'dyschromia in confetti' (following topical immunotherapy with diphenylcyclopropenone), 486 and 'infant with abnormal pigmentation'. 468 Dyspigmentation has also been associated with mosaic chromosome 5p tetrasomy 469 and with trisomy 20 mosaicism.…”
Section: Patterned Hypermelanosismentioning
confidence: 99%
“…Because they both show the same histopathological presence of basal hyperpigmentation, with no increase in numbers of melanocytes or pigmentary incontinence [4]. The term linear and whorled nevoid hypermelanosis (LWNH) was named by Kalter et al [5] in 1988, it has nearly the same clinical feature as PCZH but not always localized, and occurring within the first weeks of life.…”
Section: Discussionmentioning
confidence: 99%